Salivary cortisol in bruxing and non-bruxing children - Silvina Gabriela Cortese; Ingrid Clarisa Guitelman; Ana María Biondi (Asociación Latinoamericana de Odontopediatría, 2019)
Objective: To evaluate and compare the degree of tooth wear and salivary cortisol levels in bruxing and non-bruxing children with low and high levels of emotional instability. Methods: Data were collected from a sample of 17 healthy children with possible bruxism (B) according to the Oral Behaviors Checklist (OBC) of the Diagnostic Criteria for Temporomandibular Disorders differentiating sleep (BS) and wakefulness (BV) bruxism. They were matched by sex and age to a control group without report of bruxism (C). Five pediatric dentists calibrated for the tooth wear index (TWI) (kappa interobserver 0.94) registered the occurrence of incisor/occlusal tooth wear (probable bruxism). The dosage of cortisol was performed in a sample of morning saliva by electrochemiluminescence. Emotional instability was measured by the BFQ Big Five Questionnaire for Children (for children older than 8 years of age). Results: Sample´s mean age was: 11.3 ± 2.7, 59.6 % were female. In bruxism group 35.3 % reported BS, 35.3 % BS + BV and 29.4 % BV. No differences were found between both groups for tooth wear in primary (p=0.3858) and permanent dentition (p=0.7478). In the study group average of cortisol level was 0.181 ± 0.183 and 0.183±0.161 in control group (p=0.9863). Mean cortisol level was 0.142 ± 0.08 ug/dl for low emotional instability, and 0.149 ± 0.07 for high (p=0.0437). All the patients who had both SB and AB were in the high emotional instability group (p=0.006). Conclusions: Tooth wear in both dentitions showed no differences. Results obtained suggest that the dosage of salivary cortisol would not be relevant as a biomarker for the suggestion of bruxism in children. Patients exhibiting extreme conditions of emotional instability, showed significant differences in salivary cortisol levels and in the frequency they reported both types of bruxism.